Ku/Ka band mixers development for satellite communication systems - Zhou, Jiaoyun (2008)
This thesis focuses on Ku and Ka band mixer design, fabrication, assembly, and measurement. In order to achieve the required performance, different transmission lines or combinations of them are used for various band mixer designs.